Violence politique et légitimisme pendant la Première guerre carliste : une occasion manquée - Laetitia Blanchard (Amnis)
From 1833, in all Europe and especially in France, the First Carlist Civil War represents the confrontation of the two main government principles guiding European nations. The legitimists rely on this war to claim their privileged position on the European political stage. The First Carlist War is a factor amplifying political violence outside Spanish borders. How could this armed conflict revive the tensions between the defenders of Absolutist Regimes and the Liberals outside Spain? How could it give back hope to a legitimist community losing momentum, and how did it succeed to generate a call to violent action? This event leads to an attempt to brutalize politics and aims to reverse a ratio of power, using the parallel with the Spanish people who chose armed fight for power. Spanish Carlists become a model to imitate in all Europe. In fact, for the Legitimists, the struggle is never over, and they need to prepare the Absolutist Restoration everywhere it is still possible. This Spanish Civil War is therefore considered as an additional episode of a fight that must lead to the definitive victory of the European Legitimism.